2004
DOI: 10.1901/jeab.2004.81-297
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of Selection by Consequences

Abstract: Darwinian selection by consequences was instantiated in a computational model that consisted of a repertoire of behaviors undergoing selection, reproduction, and mutation over many generations. The model in effect created a digital organism that emitted behavior continuously. The behavior of this digital organism was studied in three series of computational experiments that arranged reinforcement according to random-interval (RI) schedules. The quantitative features of the model were varied over wide ranges in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(147 citation statements)
references
References 21 publications
4
142
0
1
Order By: Relevance
“…Variability describes the class of potential behaviors, selection describes the potentiating effects of reinforcement on behavior, and retention describes the physiological changes that permit maintenance of adaptive responses. McDowell (2004) developed a model of instrumental conditioning based on such evolutionary principles. He represented actions as ‘populations’ of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Variability describes the class of potential behaviors, selection describes the potentiating effects of reinforcement on behavior, and retention describes the physiological changes that permit maintenance of adaptive responses. McDowell (2004) developed a model of instrumental conditioning based on such evolutionary principles. He represented actions as ‘populations’ of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that all three Darwinian rules ( Figure I, Section III) must operate in order for the theory to function properly. This is obvious for selection and reproduction, but McDowell (2004) found that mutation was also necessary. He reported that without mutation, behavior becomes maladaptively perseverative, that is, it gets stuck in an arbitrary class and becomes unresponsive to environmental resources and to changes in their availability.…”
Section: Discussionmentioning
confidence: 99%
“…A Material Mechanism for the Theory McDowell (2004) suggested that the success of the evolutionary theory "means that the material operation of a biological organism . .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations